Characterization of the hepatitis C virus epidemic in Pakistan - Sarwat Mahmud (4557208) (2019)
Background With one in every 20 Pakistanis already infected, Pakistan has the second largest number of hepatitis C virus (HCV) infections globally. The aim of this study was to present a quantitative and analytical characterization of the HCV epidemic in Pakistan. Methods A standardized database of HCV antibody incidence and prevalence and HCV genotypes in all subpopulations was systematically assembled. Random-effects meta-analyses and random-effects meta-regressions were performed. Shannon Diversity Index was calculated to determine genotype diversity. Results The database included two incidence, 309 prevalence, and 48 genotype measures. Pooled mean HCV prevalence ranged between 7.0% (95% confidence interval (CI): 5.8–8.3%) in Sindh and 0.9% (95% CI: 0.1–2.4%) in Federally Administered Tribal Areas (F.A.T.A). Estimated number of chronically-infected persons ranged between 4.2 million in Punjab and 0.03 million in F.A.T.A. HCV prevalence was stable over time [adjusted odds ratio (AOR) of 1.0 (95% CI: 1.0–1.0)]. Population classification was the strongest predictor of HCV prevalence, explaining 51.8% of prevalence variation. Relative to the general population, HCV prevalence was higher in people who inject drugs [AOR of 23.8 (95% CI: 13.0–43.6)], populations with liver-related conditions [AOR of 22.3 (95% CI: 15.7–31.6)], and high-risk clinical populations [AOR of 7.8 (95% CI: 4.8–12.7)]. Low genotype diversity was observed (Shannon diversity index of 0.67 out of 1.95; 34.5%). There were only minor differences in genotype diversity by province, with genotype 3 being most common in all provinces. Conclusion Pakistan’s HCV epidemic shows homogeneity across the provinces, and over time. HCV prevalence is strikingly persistent at high level, with no evidence for a decline over the last three decades. Scale up of HCV treatment and prevention is urgently needed. Other Information Published in: BMC Infectious Diseases License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1186/s12879-019-4403-7